(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The article examines how the gender is central to an understanding women teachers occupational route and is focused on module choice processes modules at the In-Service Teacher Training Unit (Didaskaleio) department of General Pedagogy in the Universityof Patras. We examine the modules which women teachers at In-Service Teacher Training Unit of Patras chose to attend, in order to explore their interest and their professional perspectives. From the study and the program of the In-Service Teacher Training Unit of Patras of the academic years 1998-2002 we found the modules offered by the School. Then we codified the titles of the modules in order to facilitate their statistical process and we checked which modules had been taught. Next, we examined the personal portfolios of teachers per each year of attendance and we collected data with reference to the choices of their modules.